1993
DOI: 10.1055/s-0038-1649645
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Whole Blood Flow Cytometric Detection of Platelet Bound Fibrinogen on Normal Subjects and Patients with Activated Platelets

Abstract: SummaryActivated platelets can be detected by measuring platelet-bound fibrinogen in a whole blood, flow cytometric assay, using a fluorescently-conjugated polyclonal antibody.Fibrinogen binding to unstimulated platelets from normal subjects was low in this assay, as was expression of the CD63 antigen. Single cell counting of samples prepared for flow cytometric analysis showed platelet aggregates do not form during the assay procedure. Immune complexes were not seen, and fibrinogen binding to the platelets wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 11 publications
2
83
0
Order By: Relevance
“…When evaluated by flow cytometry in whole blood, platelets are sensitive to stimulation by ADP, especially with regard to fibrinogen binding. The threshold for ADP-induced enhancement of fibrinogen binding has been found to be 0.1 /imol/L, which agrees with previous data 24 - 25 and with proaggregatory effects of similar or even lower concentrations of ADP with filtragometry with whole blood in vitro. 27 The threshold for ADP-induced P-selectin expression is somewhat higher (=0.3 mol/L), but the maximum expression of this variable is also lower.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…When evaluated by flow cytometry in whole blood, platelets are sensitive to stimulation by ADP, especially with regard to fibrinogen binding. The threshold for ADP-induced enhancement of fibrinogen binding has been found to be 0.1 /imol/L, which agrees with previous data 24 - 25 and with proaggregatory effects of similar or even lower concentrations of ADP with filtragometry with whole blood in vitro. 27 The threshold for ADP-induced P-selectin expression is somewhat higher (=0.3 mol/L), but the maximum expression of this variable is also lower.…”
Section: Discussionsupporting
confidence: 91%
“…32 However, platelet contact and aggregation are avoided in the flow-cytometric assay. 25 It is possible that the thromboxane generation that occurs in citrated blood could enhance the effects of ADP, but we have shown that ADP-induced fibrinogen binding is unaffected by aspirin in citrated samples. 33 Alternatively, hirudin may inhibit low-level thrombin generation that augments the effects of ADP.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Platelets were isolated from EDTA-anticoagulated whole blood, resuspended in phosphate-buffered saline (PBS) containing 10 mM EDTA and 0.25% bovine serum albumin (BSA), and incubated with saturating concentration of mAb; the excess antibody was removed by 3 washes, followed by the addition of FITCconjugated goat anti-mouse Ig reagent (Dako). Platelet activation markers were analyzed in a whole-blood flow cytometric assay as previously described 18 using FITC-antifibrinogen (Dako), FITC-PAC-1 (BD Biosciences), or PE-anti-CD62P (Sanquin). Data were collected and analyzed using a Beckman Coulter XL-MCL flow cytometer (Beckman Coulter, High Wycombe, United Kingdom).…”
Section: Flow Cytometrymentioning
confidence: 99%
“…14,15 Briefly, fibrinogen binding to platelets was measured in unstimulated blood samples and in samples stimulated with ADP (1ϫ10 Ϫ6 mol/L; Sigma) by the binding of an FITCconjugated rabbit antibody to fibrinogen (Dako Ltd) to the platelets.…”
Section: Whole-blood Flow Cytometrymentioning
confidence: 99%